Combining calcium imaging with other optical techniques - Canepari, Marco (Cold Spring Harb Protoc, 2013)
Ca(2+) imaging is a commonly used approach to measure Ca(2+) signals at high spatial resolution. The method is often combined with electrode recordings to correlate electrical and chemical signals or to investigate Ca(2+) signals following an electrical stimulation. To obtain information on electrical activity at the same spatial resolution, Ca(2+) imaging must be combined with membrane potential imaging. Similarly, stimulation of subcellular compartments requires photostimulation. Thus, combining Ca(2+) imaging with an additional optical technique facilitates the study of a number of physiological questions. The aim of this chapter is to introduce some basic principles on how to combine Ca(2+) imaging with other optical techniques. We will focus on: 1. the design of the optics; 2. the design of experimental protocols; 3. the optical characteristics of the Ca(2+) indicators and of the additional optical probe used in combination with the Ca(2+) indicator; 4 the affinity of the Ca(2+) indicator in relation to the type of measurement. This chapter will enable the reader to devise an optimal strategy for combined optical experiments.